Application Research of Big Data Real-time Processing Technology in Smart Grid. Issue 1 (March 2021) - Zhou, Sheng; Li, Hongfa; Zhang, Jianglong; Wu, Shuling; Chen, Shiton; Wu, Xiaohua; Jin, Tao
Abstract: Big data is valuable, and big data processing technology can efficiently process massive data and get the value in big data, so the research and application of big data technology become popular nowadays. Smart grid is one of the most potential field for application of big data technology, applying big data technology to smart grid can improve the reliability and economy of smart grid. The operating conditions of power system changes rapidly, therefore, real-time processing technology became the focus of application field. This paper reviewed the data sources, data characteristics and data application scenarios of big data in smart grid, analyzed data processing modes of big data processing technology: batch processing and stream processing, and compared the realization methods of real-time big data processing, summarized the application of big data real-time processing technology in smart grid, and the challenges in the application, and finally, prospected the application of real-time big data processing technology in smart grid.